Diagnostic performance of current guidelines and postoperative outcome following surgical treatment of cystic pancreatic lesions – a 10-year single center experience. (1st December 2020) - Kovacevic, Bojan; Hansen, Mariana Cordoba; Kristensen, Thomas Skaarup; Karstensen, John Gásdal; Klausen, Pia; Storkholm, Jan; Hansen, Carsten Palnaes; Vilmann, Peter
Abstract: Objective: Pancreatic cystic lesions (PCLs) are diagnostically challenging and there are currently several different guidelines. The aim of this study was to compare diagnostic performance of the most widely utilized International Association of Pancreatology (IAP) guidelines and the recent evidence-based European guidelines and to report on postoperative outcomes following surgical treatment of PCLs. Methods: This is a retrospective single-center study of patients undergoing surgery due to a PCL between 2010 and 2019. Primary outcome was a comparison of diagnostic performance between IAP and European guidelines, measured in area under the receiver operating characteristic curve (AUC). Other outcomes included diagnostic performance of different risk features, 30-day postoperative mortality and major morbidity, final diagnosis, and overall survival. Results: We identified 137 patients, three of whom did not undergo curative surgery due to metastatic disease. Overall, there was no difference in the performance of the two guidelines with AUC values ranging from 0.572–0.610 and 0.607–0.621 for IAP and European guidelines respectively. Postoperative 30-day mortality and major morbidity were 0% (95% CI 0.0–2.7%) and 37.3% (95% CI 29.1–46.1%), respectively. More than half of the resected lesions (52.6%) were low-grade dysplastic or non-neoplastic. Conclusions: Overall, the IAP and the European guidelines performed equally, although European guidelines had a slightly higher mean specificity. Pancreatic surgery is associated with high major morbidity, and there is a need for new diagnostic tools and strategies in order to decrease the amount of overtreatment in patients with PCL.